Effectiveness of Ricosre Learning Model Using Audiovisual Media on Students' Critical Thinking Abilities and Learning Outcomes on Blood Circulatory System Material - Siti Rifaatul Mahmudah; Agung Wijaya Subiantoro (Riviera Publishing, 2025)
The implementation of innovative learning is essential for enhancing the quality of education, particularly in fostering students' critical thinking skills. This study endeavors to assess the effectiveness of the RICOSRE learning model, supplemented by audiovisual media, on students' critical thinking abilities and learning outcomes in the context of circulatory system material. The research methodology employed was quasi-experimental, utilizing a simple random sampling design. The research sample comprised two classes: the experimental class that engaged with the RICOSRE learning model supported by audiovisual media, and the control class that adhered to conventional learning methods. Data were acquired through tests assessing learning outcomes, observation sheets, and student feedback questionnaires. Data analysis was conducted using both descriptive and inferential statistical tests, specifically employing the independent sample t-test. The findings demonstrated a significant difference between the RICOSRE learning model supported by audiovisual media and conventional learning methods regarding critical thinking skills, indicated by a significance value of 0.000, and student learning outcomes, with a significance value of 0.006 at a 5% significance level. This outcome suggests that using the RICOSRE learning model, augmented by audiovisual media, is more effective in enhancing students' critical thinking skills and learning outcomes than traditional methods.